CORPORATE STEREOTYPING OF WOMEN AT WORK PLACE - Thankachan, Steffi; Riaz, Sadia (PEOPLE: International Journal of Social Sciences, 2018)
Stereotyping is an issue faced by women across the world. There have always been clear distinct roles for women and men in the society because of nature-versus-nurture debate that has haunted the humanity for very long. The main motive of the research is to test the effects of women stereotyping at their work places and how it could affect their confidence level in while moving onto the higher managerial positions. It is reported that women held under a quarter (24%) of senior roles across the world in 2016, which is only 3% of increase from 2011. Furthermore, one third (33%) of global businesses had no women in senior management roles, a number which has stayed stagnant since 2011. It is feared that in given circumstances and level of growth, women will not reach parity with men until 2060. The primary reason attributed to this discrimination is stereotyping faced by women in the form of gender inequalities, biased leadership, traditions and culture. The purpose of the study is to examine existence of this phenomena and how it may affect self-confidence, work performance of women working at entry and senior management level positions in UAE. The research design was based on primary data collection using questionnaire method and randomized sampling techniques were deployed. Data analysis was done using SPSS v. 2.0 and techniques used were Pearson correlation, post hoc test, and independent t -test. The study was able to substantiate the ongoing perception that women indeed are stereotyped in a corporate world, even though there is a boost in female workers considering the past reports. It is unfortunate that very few women are given senior roles and results also showed that even though women had accumulated 10+ years of work experience, they still faced major stereotype threats hindering their career advancement to reach higher level.